PEMBERDAYAAN PELAKU UMKM KERAJINAN ANYAMAN BAMBU - Fajar Fajar; Romli Gafur; Muhatta Muhatta; Veronika Joan Jasmine; Haris Ibnu Zaki; Tubagus Riki F.I; Siti Juariyah; Ahmad Heryadi; Baihaki Baihaki; Basrowi Basrowi; Furtasan Ali Yusuf (Gapenas Publisher, 2023)
Handicraft MSMEs in the form of woven bamboo have begun to disappear, many of these handicraft MSMEs are no longer productive due to the very cheap price of handicrafts. Even though this is a national heritage that can be developed, the relatively cheap price makes craftsmen feel less enthusiastic in producing woven bamboo. In addition, the scarcity of raw materials is also an obstacle in itself. For this reason, it is necessary to increase creativity in creating woven shapes so that they can have high economic value, then they can also use other existing materials into useful crafts. The purpose of this community service is to advance MSMEs in Tegal Maja Village so that they can develop more in terms of marketing to advance the economy in Tegal Maja Village. This method of community service is carried out using handicraft training methods. Data collection through pre-test and post-test. The results of community service show that there are significant changes in the creativity of processing woven into better work and high economic value